Pengelolaan Objek Wisata Pantai Bontolan Di Desa Bone Baru Banggai Laut Sulawesi Tengah - Wiranto, Muh.; Rachman, Ellys; Antu, Yahya (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
This study aims to determine the management of Bontolan beach tourism objects in Bone Baru Village, Banggai Utara District, Banggai Laut Regency. This research method uses a descriptive qualitative approach. Data collection techniques are carried out through in-depth interviews with a number of informants, observation and recording of secondary data related to the researcher's problems. The results of the study concluded that the management in terms of planning is quite optimal. This can be seen from the readiness in planning the arrangement of tourist objects. The objects in terms of implementation is quite optimal because the readiness of the committees selected by the local village government. The management of supervision is optimal. from the problems that are directly handled appropriately so that visitor satisfaction can be met properly. It is recommended that better planning be carried out on improving facilities for tourist objects by considering the suitability of visitors' tastes. It is necessary to make efforts to implement both human resources and physical resources owned so that it can be more optimal in providing services to visitors. It is necessary to improve the village government's supervisory function regarding the activities of the Bontolan Beach object in Bone Baru Village, especially by adding existing facilities for the convenience of future visitors.